Perbandingan Pengetahuan Remaja Tentang Dampak Kehamilan pada Remaja Sebelum dan Sesudah Diberikan Pendidikan Kesehatan Reproduksi Melalui Media Video - Firda Thursyana; Puspa Sari; Merry Wijaya (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
A wide range of sexual and reproductive health problems occur among adolescents. The issue is high on teenage pregnancy on nowadays are teenagers. Based on studies of teenage pregnancies in Sumedang-related parenting parents, the influence of friends and dating, as well as media exposure information. This study aims to compare the knowledge of teenagers before and after the given health education about the impact of pregnancy on teens through the medium of video. The methods used in this research was quasi experimental research method with the concept of one group pre test and post test design. Development by way of doing a one time measurement before and after health education was given. Sampling is done using a stratified random sampling technique. The number of samples that used as many as 52 respondents ages 17-19 years as a schoolgirl SMAN Jatinangor. Instrument research using questionnaires with retrieving the data directly. This research using univariate analysis and bivariat with kolmogorov-smirnov test for normality and Wilcoxon test. Research time on July 28, 2016. The results of this research is that before health education 71.2% of respondents knowledgeable enough and after health education changed to 94.2% respondents have knowledge well. There is a difference of knowledge teenagers before and after health education is provided through video on the impacts of teenage pregnancies with p value 0.000. Summary of the research is given after the teenager's knowledge of health education through the medium of video is higher than before given health education through the medium of video.